Comparative susceptibility of two Neotropical predators, Eriopis connexa and Chrysoperla externa, to acetamiprid and pyriproxyfen: Short and long-term effects after egg exposure - Rimoldi, Federico (2017)
Compatibility assessments between selective insecticides and the natural enemies of pests are essential for integrated-pest-management programs. Chrysoperla externa and Eriopis connexa are two principal Neotropical predators of agricultural pests whose conservation in agroecosystems requires a toxicity evaluation of pesticides to minimize the impact on those beneficial insects on the environment. The objective of this work was to evaluate the toxicity of the insecticides pyriproxyfen and acetamiprid on C. externa and E. connexa eggs exposed to the maximum recommended field concentrations of each along with three successive dilutions. The survival and the immature developmental time were assessed daily until adulthood and the mean survival time calculated over a 10-day period. The cumulative survival of E. connexa was reduced at all concentrations of both insecticides, while that of C. externa was significantly decreased by ≥50 mg L−1 of acetamiprid and ≥37.6 mg L−1 of pyriproxyfen. In both species, the reductions occurred principally on the eggs and first larval instar. Survival curves, in general, differed from those of the controls, with the mean survival time of E. connexa being significantly shorter in insecticides treatments than that of the controls. Certain concentrations of each of the insecticide lengthened the egg and first-larval-instar developmental periods of E. connexa and C. externa, respectively. Also, pyriproxyfen reduced the first-larval-instar period and lengthened the fourth of E. connexa. Acetamiprid was more toxic to E. connexa than to C. externa at the two highest concentrations. Conversely, at those same concentrations of pyriproxyfen, the relative toxicity to the two species was reversed. The present work represents the first investigation on the comparative susceptibility of two relevant Neotropical biological control agents to acetamiprid and pyriproxyfen. Also, it highlights the necessity of assessing long-term effects in the compatibility studies between natural enemies of agricultural pests and insecticides.